Estudo de governo eletrônico de Moçambique e do Estado de São Paulo- Brasil: uma discussão sobre as políticas - Adelio Segredo Dias (2012)
The thesis aims to study the policies of e-government of Mozambique and the State of São Paulo - Brazil, as a subdomain of public information policy. The study that objectively describes the principles and configurations inherent in the relation between State and Society in the context of e-government policy, has as its main issue to know in which parameters such policies may assist in this regard and wonder over what approach should be prescriptively adopted in its implementation for the development of an information culture. In order to conduct the study and achieve the objectives outlined, the study is an underlying theoretical framework that discusses the issues of state reform and public policy information, seeking to understand their role in state-society relations. Further, it discusses the concept of e-government in order to fit it to the theme of the thesis. The proposed methodology lies in the plane of a qualitative study plan whose main technique was the case study and data collection is limited by the interviews and documentary analysis. These results indicate that for the case of Mozambique, the implementation of e-government policy has neglected some aspects contained in the formulation phase, including those related to the size of information culture, which is why the process has some inconsistencies. And in the State of São Paulo, the results show that the success of the policy due to the commitment of the government with regard to the model outlined in the formulation phase, as well as the process of ongoing assessment aimed at measuring the interest and understanding of politics by citizens. However, on the other hand, the survey results show that the e-government of the State of São Paulo needs to flow to the stage of greater citizen participation in government processes and an effective integration between the various public sectors: municipal, estate and federal regulations.